Internalisasi Nilai-nilai Pendidikan Islam dalam Keluarga Muslim Milenial: Studi Fenomenologis atas Surah Luqman Ayat 12–19 - Muhammad Farij Al-Kahfi; Anisa Dwi Makrufi; Amri Saputra; Dwi Ratnasari (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to describe the implementation of Islamic educational values in Surah Luqman verses 12–19 among millennial Muslim families in Kasihan District and to identify the challenges faced in the internalization process. Using a qualitative phenomenological approach, data were collected through in-depth interviews and observations with six families. The findings indicate that the values of aqidah, morality, and worship are implemented through prayer routines, respect toward parents, communal prayer, and explanations of worship meanings. However, families face challenges such as technological influence, shifting communication patterns between parents and children, and limited religious knowledge. These factors affect the consistency of Islamic value habituation in daily life. The study concludes that while the values of Surah Luqman have been applied positively, optimal implementation requires strengthened religious literacy, proper technology management, and broader community support.